Analisis Efektivitas Sistem Pemindahan Sampah “Surung Sintak” di Kota Banjarmasin - Bella Nadya Safitri; Muhammad Firmansyah; Andy Mizwar; Muhammad Abrar Firdausy (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2026)
The narrow area and dense population in Banjarmasin have made it difficult to find land to build TPS in each village so that one TPS can serve several villages. The uneven distribution of TPS in each urban villages resulted in several residential areas being relatively far away to reach the available TPS. These problems made the Banjarmasin City Environment Service create a new innovation, namely